IMPROVING TEACHER SKILLS IN MAKING POWER POINT MEDIA THROUGH IN HOUSE TRAINING - Siti Rostima (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study is motivated by the teachers’ skills in teaching especially the lack of learning media used that encourage researcher to conduct training through in-house training in order to improve teacher skills in making power point learning media. This study was an action research conducted at SDN 38 Mandau with the subjects were 6 teachers. Technique of analysing data used assessment guidelines. The results of the study showed that in cycle I the teacher's skill in making power points was 2.35 which was a poor category, after improvement the teachers’ skills had increased in cycle II to 3.08 which was included in good categories. Based on the results of the study, it can be concluded that the teachers’ skills at SDN 38 Mandau have increased in making power point media through in-house training.